2021
DOI: 10.1128/msystems.00986-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis Provides Insights into the Evolution and Genetic Diversity of Community-Genotype Sequence Type 72 Staphylococcus aureus Isolates

Abstract: Understanding the evolution and dissemination of community-genotype ST72 Staphylococcus aureus isolates is important, as isolates of this lineage have rapidly spread into hospital settings and caused serious health issues. In this study, we first carried out genome-wide analysis of 107 global ST72 isolates to characterize the evolution and genetic diversity of the ST72 lineage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(43 reference statements)
2
5
0
Order By: Relevance
“…selu was suspected to be undectable due to its uncertain emetic activity in some studies. What’s more, the egc cluster was observed in all CC5, CC9, CC20, CC25, CC72 and ST672, but occasionally present in CC1, all of which (except for ST672) were reported in other previous studies but with various spa types [ 28 30 ]. These data suggested that a close connection between the egc cluster and the clonal genetic background.…”
Section: Discussionsupporting
confidence: 64%
“…selu was suspected to be undectable due to its uncertain emetic activity in some studies. What’s more, the egc cluster was observed in all CC5, CC9, CC20, CC25, CC72 and ST672, but occasionally present in CC1, all of which (except for ST672) were reported in other previous studies but with various spa types [ 28 30 ]. These data suggested that a close connection between the egc cluster and the clonal genetic background.…”
Section: Discussionsupporting
confidence: 64%
“…The other emerging lineages observed in our results belong to ST72 and include the ST72-SCCmecIV and ST72-SCCmecVI. The former is a genetic lineage previously described in community-associated infections in South Korea (45)(46)(47). In contrast, to the best of our knowledge, this is the first description of ST72-SCCmecVI.…”
Section: Discussionmentioning
confidence: 97%
“…ST188 is the major lineage causing multiple host species infections in Shanghai, China ( Wang et al, 2018 ). Furthermore, both international transmission of ST72 isolates and interregional transmission within China were observed, with t148 being the most common spa typing ( Zhou et al, 2021 ). Although ST243 has fewer reports, it may colonize patient-to-contaminated healthcare worker transmission in hospital settings ( Ferreira et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%